2009
DOI: 10.2105/ajph.2006.098582
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Recent HIV Infection Among Seattle-Area Men Who Have Sex with Men

Abstract: There is a need to improve efforts to promote condom use with casual partners, regardless of their partner's HIV status. New strategies to control methamphetamine use in MSM and to reduce risk behaviors related to meeting partners at high-risk venues are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 44 publications
4
55
1
Order By: Relevance
“…[23][24][25][26] To lessen recall bias, participants were asked to recall details about sex partners and risk behaviors during the past 6 months rather than a longer period of time. Third, due to the small sample size and the recruitment locations, 17 the study population may not be representative of MSM in the broader community who are recently diagnosed with HIV. Finally, there are potential limitations in our use of a cross-sectional design and the associated classification of delayed and non-delayed testers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25][26] To lessen recall bias, participants were asked to recall details about sex partners and risk behaviors during the past 6 months rather than a longer period of time. Third, due to the small sample size and the recruitment locations, 17 the study population may not be representative of MSM in the broader community who are recently diagnosed with HIV. Finally, there are potential limitations in our use of a cross-sectional design and the associated classification of delayed and non-delayed testers.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment and study procedures have been detailed elsewhere. 17 Briefly, potential participants were passively referred to the study after testing for HIV at the PHSKC sexually transmitted diseases (STD) and HIV/AIDS Program (HAP) clinics, HAP community outreach testing sites, and two university HIV clinics. MSM were eligible if they were age 18 or older, reported sex with men during the preceding 6 months, and were able to complete the interview in English.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methamphetamine is commonly used in conjunction with sexual risk-taking (Buchacz et al 2005;Hirshfield et al 2004;Molitor et al 1998;Paul et al 2005;Shoptaw et al 2005;Thiede et al 2008). In a longitudinal study of urban MSM, Koblin and her colleagues (Koblin et al 2006) reported that use of amphetamines nearly doubled a study participant's chance of HIV seroconversion (hazard ratio of 1.96), but use of marijuana, poppers, hallucinogens, or cocaine or crack were not associated with seroconversion in multivariate analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, advances in HIV testing have made it easier to distinguish individuals with evidence of recent HIV infection from persons infected at an unknown time in the past (Janssen et al 1998;Kothe et al 2003;Rawal et al 2003). By using these assays, it is possible to design studies that can identify factors associated with recent HIV infection (Thiede et al 2008).…”
Section: Introductionmentioning
confidence: 99%